Use of Wood Macerated Elements for Classification of Salix L. Species in Kurdistan Region- Iraq - Shahbaz, Saleem E.; Abdulrahman, Shamiran S. (Science Journal of University of Zakho, 2015)
Characters of wood macerated elements were investigated for taxonomic application. Wood samples from 5 stems of each Salix acmophylla, S. alba, S. babylonica, S. aegyptiaca, and S. Purpurea were collected from different geographical regions of kurdistan to clasp most possible variation. Wood of most species contains vessel elements described of primitiveness together with those descriptive of more or less advanced. Vessels of different species are similar in possessing the simple perforation plate. The differences are huge in vessel length and vessel width and hence in length/width ratio. Differences are also huge in vessel type or the end wall characters of vessel elements described of primitiveness and advancement, occurrence or absence of spiral thickening, cell walls pitting intensity and distribution within and between species. All these features are found to be important for providing taxonomic application. Libriform fibers are the only fibers present in the wood of this genus, no fiber trachieds occur. All species have fibers possessing dentition, almost exclusively at the distal parts, very rarely situated throughout the fiber length. Dentition morphological structure, distribution, size and orientation form important diagnostic characters